Student-instructor workload in simulated and real flight - Weelden, E. van; Alimardani, M.; Wiltshire, T.J.; Roy, R.N.; Dehais, F. (My University, 2024)
In the context of flight training, monitoring the mental workload of both students and instructors is important for a holistic view of overall training progress and evaluation. This study explored the subjective workload experienced by student pilots and their instructors during simulated and real flight, and how it was affected by their type of cooperation: 1) pilot monitoring (PM), in which the student was the co-pilot, observing and assisting the instructor, and 2) pilot flying (PF), in which the student was flying the aircraft and the instructor served as the co-pilot. Eight student pilots and two instructors participated in our study. The results showed that real flight induced higher subjective workload for student pilots and instructors than simulated flight, as did PF compared to PM.